Strategic Safety Stock Level For High Import Dependence Manufacturing Supply Chain For Enhanced Force Majeure Preparedness - Dong Eon Kim; Desy Anisya Farmaciawaty; Adirizal Nizar (Green Publisher Indonesia, 2025)
This study aims to determine the appropriate safety stock levels to enhance PT. Sukses Pharmapack’s preparedness for force majeure events and ensure operational continuity. By analyzing demand patterns over a five-year period, the research evaluates the effectiveness of safety stock in mitigating supply chain disruptions through scenario-based simulations. A mixed-method approach is applied, combining qualitative insights from key stakeholders with quantitative analysis of demand and lead time data. Statistical techniques such as mean, standard deviation, Z-score, and coefficient of variation are used to assess demand and lead time variability, while the Economic Order Quantity (EOQ) model with probability is employed to calculate optimal order quantities and safety stock levels. The findings indicate that a 30% increase in both demand and lead time results in the highest safety stock levels, improving service levels but raising inventory holding costs. Conversely, lower demand and shorter lead times reduce safety stock requirements but increase the risk of stockouts. The study is limited to a single product and supplier, which may restrict generalizability. Future research should explore multiple products and dynamic market conditions, implementing adaptive inventory policies with real-time demand monitoring.